Mathematical modeling of the charging process of Li-S batteries by incorporating the size-dependent Li2S dissolution. (10th February 2019) - Xiong, C.; Zhao, T.S.; Ren, Y.X.; Jiang, H.R.; Zhou, X.L.
Abstract: During the discharge process of lithium-sulfur batteries, the nucleation and growth of Li2 S precipitates result in a non-uniform Li2 S particle size distribution, significantly affecting the charging process. However, a uniform Li2 S distribution at the initial state of the charging process of the batteries is assumed in the models reported in the literature, leading to an unrealistic simulation of the charging process. To address this issue, we propose a one-dimensional transient mathematical model, which incorporates the size-dependent Li2 S dissolution and redox mediation reaction between dissolved polysulfides and Li2 S particles into the charging process. Simulation results show that the dissolution rate of large Li2 S particles is suppressed at a lower potential due to the small specific surface area, while the smaller Li2 S particles are electrochemically oxidized into dissolved polysulfides first, which further act as the redox mediators to promote the oxidation of larger Li2 S particles. Capturing these effects enables an excellent agreement between the predicted and measured charging voltage profiles. Moreover, the effects of particle sizes and redox mediation reaction rates are studied. It is revealed that the optimal amount of smaller-sized Li2 S particles and suitable redox mediation reaction rate allow for a lower charging over-potential. Furthermore, it is shown that the effect of redox mediation rates on the dissolution of Li2 S large particles exerts a significant influence on the charging process. Graphical abstract: A lithium-sulfur (Li-S) battery model incorporating the size-dependent effect and redox mediation reaction is developed, describing the mechanisms during charging process. Image 1 Highlights: A transient one-dimensional charging model for Li-S batteries is developed. Size-dependent Li2 S dissolution is depicted. The redox mediation reaction between dissolved polysulfides and Li2 S particles is considered. Strategies to decrease the charging over-potential are discussed.